EFEKTIVITAS PROGRAM IDENTITAS KEPENDUDUKAN DIGITAL DALAM MEMPERMUDAH ADMINISTRASI KEPENDUDUKAN (STUDI PADA DISDUKCAPIL KABUPATEN TEBO) - Fajar Ifan Dolly; Nur Yami Sari (Nusantara Hasana Journal, 2025)
This study aims to see the effectiveness of the IKD program and the readiness of the Population and Civil Registry Office and to find out what obstacles there are in implementing the IKD program in Tebo Regency. The research uses a descriptive method with a qualitative approach with the population in this study being all employees of the Tebo Regency Population and Civil Registry Service and the community of IKD users with samples determined using the techniquepuroposive sampling and incidental sampling. For the data source of this study, it comes from primary data and secondary data by applying data analysis techniques according to Miles and Huberman which start from the stages: data collection, reduction, presentation, ending with drawing conclusions. The results of the study indicate that the effectiveness of the IKD program in facilitating and accelerating population administration in Tebo Regency has not been effective. This is because the objectives set in the rules are not running properly. From several indicators of program effectiveness, it can be seen that from the indicators of program target accuracy and program socialization, it has not been fully implemented in accordance with the achievement of objectives. It is recommended to the Tebo Regency Population and Civil Registry Office, to be committed and consistent in implementing the rules, implementing more massive socialization, and giving sanctions to certain actors in making the IKD program a success, this is so that the community can immediately use the IKD application to support the smoothness and ease of population administration.